Looking for answers to the food security problem: India under current compulsions - Nilabja Ghosh; Basudeb Guha-Khasnobis (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
Food insecurity at the household level has become unacceptable in India where the economy is growing at high rates and food sufficiency is already achieved at the macro-level. Food security has always been an important issue in the Indian political economy and was addressed by numerous poverty-eradication and rural development programmes that emerged and evolved with time. In recent times of liberalization, the programmes are intended to be more targeted and integrated with other social objectives through innovative designing. In particular, the government is all set to using public works programme, which is nothing new to India or other developing countries, as a nationwide instrument to confer earning opportunity to rural people backed by legal reinforcement. This paper reviews the strategies and instruments in India that impinge on household food insecurity. The paper also examines how far the existing public works programmes in select four states target the households that are likely to be food insecure.
Keywords: I38; D63; H75; 330; food insecurity; public works programmes; poverty alleviation; cereal consumption; Nahrungsmittelversorgung; Armutspolitik; Öffentliche Arbeiten; Indien